Inventarisasi Jamur yang Diisolasi Dari Daun Mentimun (Cucumis sativus L.) Bergejala Sakit Di Desa Rasau Jaya,Kalimantan Barat - Rahmawati, Nela Amanda, Mukarlina (Universitas Tanjungpura, 2017)
Cucumber (Cucumis sativus L.) often faces problem with presence of pest organism causing symptoms of disease progression. One of the most symptomatic part is the leaf. This research was conducted to find out the types of fungi isolated from the leaves of cucumber (Cucumis sativus L.) symptomatic of disease in Rasau Jaya village, West Kalimantan. Isolation of fungi from symptomatic cucumber leaves was done by direct planting on the media of PDA (Potato Dextrose Agar). The result of this research indicate that three genera of fungi: members of the genera Aspergillus, Colletotrichum and Rhizomucor.